Islam and democracy perspectives on the Arab Spring - Noi, Aylin Unver (Cambridge Scholars Publishing, 2013)
This book explores changes in the Middle East and North Africa in the aftermath of the Arab Spring by giving a brief history of developments. It discusses the types of challenges that these countries have faced, and continue to face, during their democratic transitions. It offers readers a more complete overview of the complex and interrelated aspects of the Arab Spring and the roles of Islam and democracy in these ongoing developments.